Pengaruh Kedisiplinan Dan Motivasi Belajar Siswa Terhadap Hasil Belajar Baca Tulis Al-Qur'an Kelas VII Di SMP H. Isriati Semarang - Wahid Hakim Azzaky; Raharjo Raharjo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the influence of student discipline and learning motivation on the learning outcomes of reading and writing the Al-Qur'an in class VII at SMP H. Isriati. This research is field research with a quantitative approach using correlational techniques. The research subjects were 77 students in class VII of H. Isriati Middle School with a research sample of 50 students. The data collection methods used were questionnaires and documentation and used multiple linear regression analysis. This research concludes that learning discipline has a significant effect on learning outcomes, learning motivation has a negative and significant effect on learning outcomes. 3) Discipline and learning motivation simultaneously have a significant effect on the learning outcomes of reading and writing the Al-Qur'an for class VII students at SMP H. Isriati.